MESSAGE OF DA’WAH AND THE EXISTENCE OF LENGGER DANCE CULTURE IN WONOSOBO: PESAN DAKWAH DAN EKSISTENSI BUDAYA TARI LENGGER DI WONOSOBO - SHAFRANI, KHARISMA (IQTIDA : Journal of Da'wah and Communication, 2025)
The Lengger dance is a traditional dance that developed in the Wonosobo area, Central Java. This dance was originally performed by a kakung (old man) wearing a mask. However, as time has progressed, this dance is danced by two women who are beautifully and beautifully made up. The research on the messages of da'wah and cultural existence in the lengger dance in Wonosobo aims to determine what da'wah messages are contained in the lengger dance and how the lengger dance exists from the past to the present. This research uses a qualitative method with a field study approach. The results of this study indicate that the lengger dance is a dance performed by Sunan Kalijaga who wears a mask to conceal his identity. This dance contains a da'wah message that humans always remember God. The lengger dance is usually performed at celebrations, thanksgiving, village slametan, welcoming dances, and rituals during the month of Suro.